Nitride light emitting diode epitaxial wafer and preparation method thereof
By introducing a combined layer, including an electron trap layer and a polarization layer, the problems of Stark effect and electron overflow in traditional structures are solved, and the luminous efficiency is improved.
Patent Information
- Application Number
- CN202411358544.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-27
AI Technical Summary
In the traditional GaN-based LED epitaxial structure, the Stark effect and electron overflow problems caused by the polarization effect reduce the luminescence efficiency.
A combined layer is introduced between the N-type layer and the electron barrier layer, which includes an electron trap layer and a polarization layer that grows sequentially from bottom to top. The electron trap layer is an alternating structure of Mg-doped ScGaN layer and BGaN layer. The polarization layer includes an N-plane polar quantum well layer, an N-plane polar quantum barrier layer, a Ga-plane polar AlGaN layer and an N-plane polar Si-doped InAlGaN layer.
Through the improved epitaxial sheet structure, the effective recombination efficiency between holes and electrons is increased, electron overflow and Stark efficiency of multiple quantum wells is reduced, thereby improving the luminous efficiency of GaN-based LEDs.
Smart Images

Figure CN119421571A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor devices, and in particular to a nitride light emitting diode epitaxial wafer and a preparation method thereof. Background Art
[0002] Semiconductor light emitting diodes have the advantages of small size, durability, strong controllability of light-emitting bands, high light efficiency, low heat loss, low light decay, energy saving and environmental protection. They are widely used in full-color display, backlight source, signal light, optoelectronic computer interconnection and short-distance communication, and are gradually becoming a hot spot in the current research field of electronic power.
[0003] Gallium nitride materials have a series of advantages such as wide band gap, high electron mobility, high thermal conductivity and high stability, so they have wide applications and huge market prospects in high-brightness blue light-emitting diodes. The main structures of the traditional GaN-based LED epitaxial structure include substrate, buffer layer, N-type layer, multi-quantum well layer, electron blocking layer, P-type layer and P-type contact layer. Due to the inherent polarization effect of GaN-based materials, the Stark effect will cause the band bending in the multi-quantum well layer of the traditional GaN-based LED epitaxial structure, reduce the overlap of wave functions, thereby reducing the effective recombination efficiency of holes and electrons, resulting in reduced luminous efficiency; and because electrons migrate faster than holes and are more numerous, electrons that have not been recombined will produce electron overflow, reduce antistatic ability, and further reduce luminous efficiency. Therefore, how to improve the luminous efficiency of GaN-based LEDs is the focus of the LED industry and the main goal of current research and development. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to propose a nitride light-emitting diode epitaxial wafer, which can increase the effective recombination efficiency of holes and electrons, reduce electron overflow and reduce the Stark efficiency of multiple quantum wells, thereby improving the luminous efficiency of GaN-based LED chips, solving the problem of low luminous efficiency of current GaN-based LEDs.
[0005] Another object of the present invention is to provide a method for preparing a nitride light emitting diode epitaxial wafer, which is used to prepare the above-mentioned nitride light emitting diode epitaxial wafer.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A nitride light-emitting diode epitaxial wafer comprises a substrate, and further comprises a buffer layer, an N-type layer, a combination layer, an electron blocking layer and a P-type layer sequentially stacked on the substrate;
[0008] The combined layer includes an electron trap layer and a polarization layer which are stacked and grown sequentially from bottom to top;
[0009] The electron trap layer includes a Mg-doped ScGaN layer and a BGaN layer that are periodically and alternately grown from bottom to top;
[0010] The polarization layer comprises an N-face polarity quantum well layer, an N-face polarity quantum barrier layer, a Ga-face polarity AlGaN layer and an N-face polarity Si-doped InAlGaN layer which are grown periodically and alternately from bottom to top.
[0011] As an improvement of the above solution, the thickness of the N-face polar Si-doped InAlGaN layer is 3 to 3.5 nm;
[0012] The doping concentration of Si element in the N-face polar Si-doped InAlGaN layer 424 is 1×10 14 ~5×10 16 atoms / cm 3 .
[0013] As an improvement of the above solution, the proportion of Al component in the Ga-face polar AlGaN layer is 0-0.3, and in the periodic growth, the Al component in the Ga-face polar AlGaN layer presents an increasing trend in each period;
[0014] The thickness of the Ga-face polar AlGaN layer is 0-110 nm.
[0015] As an improvement of the above solution, the N-side polar quantum well layer is an InGaN layer with a thickness of 2 to 3.5 nm;
[0016] The N-side polar quantum barrier layer is a HGaN layer, and H is any one or more combinations of In, Al, B, Sc and Y; the thickness of the N-side polar quantum barrier layer is 9-16 nm.
[0017] As an improvement of the above solution, the thickness of the Mg-doped ScGaN layer is 3-5 nm, and the doping concentration of the Mg element in the Mg-doped ScGaN layer is 1×10 14 ~1×10 16 atoms / cm 3 ;
[0018] The thickness of the BGaN layer is 3-5 nm.
[0019] As an improvement of the above solution, the number of cycles of the alternating growth of the electron trap layer is 3 to 6;
[0020] The number of cycles of the alternating growth of the polarization layers is 7 to 11;
[0021] The growth temperature of the combined layer is 780-1000° C., and the growth pressure is 100-500 torr.
[0022] As an improvement of the above solution, the electron blocking layer is an AlInGaN layer, the Al component in the electron blocking layer accounts for 0.005-0.1, and the In component accounts for 0.01-0.2;
[0023] The thickness of the electron blocking layer 5 is 10-40 nm, the growth temperature is 900-1000° C., and the pressure is 100-300 torr.
[0024] Correspondingly, the present invention also provides a method for preparing a nitride light-emitting diode epitaxial wafer, which is used to prepare the above-mentioned nitride light-emitting diode epitaxial wafer, comprising the following steps:
[0025] (1) providing a substrate;
[0026] (2) depositing a buffer layer on the substrate;
[0027] (3) depositing an N-type layer on the buffer layer;
[0028] (4) depositing a combined layer on the N-type layer;
[0029] (5) depositing an electron blocking layer on the combined layer;
[0030] (6) Depositing a P-type layer on the electron blocking layer.
[0031] As an improvement of the above scheme, before depositing the N-type layer on the buffer layer in step (3), the step further includes pre-treating the substrate on which the buffer layer has been deposited. The pre-treating method is as follows:
[0032] The substrate coated with the buffer layer is transferred into the MOCVD device, pretreated for 1 to 10 minutes in a H2 atmosphere at a treatment temperature of 1000 to 1200°C, and then the substrate is nitrided.
[0033] As an improvement of the above solution, the N-type layer includes an undoped GaN layer and a Si-doped n-type GaN layer, and step (3) of depositing the N-type layer on the buffer layer includes the following steps:
[0034] a. Depositing the non-doped GaN layer on the buffer layer; wherein the growth temperature of the non-doped GaN layer is 1050° C. to 1200° C., the growth pressure is 100 to 600 torr, and the thickness is 1 to 5 μm;
[0035] b. Depositing the Si-doped n-type GaN layer on the non-doped GaN layer; wherein the Si-doped n-type GaN layer has a growth temperature of 1050° C. to 1200° C., a growth pressure of 100 torr to 600 torr, a thickness of 2 to 3 μm, and a Si doping concentration of 1×10 19 ~5×10 19 atoms / cm 3 .
[0036] The implementation of the present invention has the following beneficial effects: Compared with the conventional LED epitaxial structure using a conventional multi-quantum well layer between the N-type layer and the electron blocking layer, the nitride light-emitting diode epitaxial wafer of the present technical solution improves and optimizes the overall structure, and sets a combination layer between the N-type layer and the electron blocking layer. Among them, the combination layer includes an electron trap layer and a polarization layer that are stacked and grown from bottom to top; the electron trap layer is an alternating structure of Mg-doped ScGaN layer and BGaN layer; the polarization layer includes an N-face polarity quantum well layer, an N-face polarity quantum barrier layer, a Ga-face polarity AlGaN layer, and an N-face polarity Si-doped InAlGaN layer that are periodically and alternately grown from bottom to top. By improving and optimizing the structure of the epitaxial wafer, the present technical solution can increase the effective recombination efficiency of holes and electrons, reduce electron overflow and reduce the Stark efficiency of the multi-quantum well, thereby improving the luminous efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a schematic structural diagram of a nitride light-emitting diode epitaxial wafer according to Example 1 of the present invention;
[0038] Among them, substrate 1, buffer layer 2, N-type layer 3, combination layer 4, electron blocking layer 5, P-type layer 6, electron trap layer 41, polarization layer 42, Mg-doped ScGaN layer 411, BGaN layer 412, N-face polar quantum well layer 421, N-face polar quantum barrier layer 422, Ga-face polar AlGaN layer 423, N-face polar Si-doped InAlGaN layer 424. DETAILED DESCRIPTION
[0039] To make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0040] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. Raw materials used without specifying the manufacturer are all conventional products that can be obtained through commercial purchase.
[0041] like Figure 1 As shown, the nitride light-emitting diode epitaxial wafer of the present technical solution includes a substrate 1, and also includes a buffer layer 2, an N-type layer 3, a combination layer 4, an electron blocking layer 5 and a P-type layer 6 sequentially stacked on the substrate 1;
[0042] The combined layer 4 includes an electron trap layer 41 and a polarization layer 42 which are stacked and grown sequentially from bottom to top;
[0043] The electron trap layer 41 includes a Mg-doped ScGaN layer 411 and a BGaN layer 412 that are periodically and alternately grown from bottom to top;
[0044] The polarization layer 42 includes an N-face polarity quantum well layer 421, an N-face polarity quantum barrier layer 422, a Ga-face polarity AlGaN layer 423 and an N-face polarity Si-doped InAlGaN layer 424 which are periodically and alternately grown from bottom to top.
[0045] It is worth noting that, compared with the conventional LED epitaxial structure using a conventional multi-quantum well layer between the N-type layer 3 and the electron blocking layer 5, the nitride light-emitting diode epitaxial wafer of the present technical solution improves and optimizes the overall structure, and sets a combination layer 4 between the N-type layer 3 and the electron blocking layer 5. Among them, the combination layer 4 includes an electron trap layer 41 and a polarization layer 42 that are stacked and grown from bottom to top; the electron trap layer 41 is an alternating structure of a Mg-doped ScGaN layer 411 and a BGaN layer 412; the polarization layer 42 includes an N-face polarity quantum well layer 421, an N-face polarity quantum barrier layer 422, a Ga-face polarity AlGaN layer 423, and an N-face polarity Si-doped InAlGaN layer 424 that are periodically and alternately grown from bottom to top. By improving and optimizing the structure of the epitaxial wafer, the present technical solution can increase the effective recombination efficiency of holes and electrons, reduce electron overflow and reduce the Stark efficiency of the multi-quantum wells, thereby improving the luminous efficiency.
[0046] Specifically, in the N-face polar quantum well layer 421 of the present technical solution, the direction of the polarization field is opposite to the direction of the external bias field, and the polarization field weakens the total electric field in the quantum well, causing the quantum well energy band to be flattened, and the electron-hole wave function to overlap more, thereby improving the luminescence efficiency of the quantum well. At the same time, in the present technical solution, the N-face polar quantum well layer 421, the N-face polar quantum barrier layer 422, and the N-face polar Si-doped InAlGaN layer 424 are all N-polar, alternating with the Ga-face polar AlGaN layer 423, which can reduce the spontaneous polarization effect, reduce non-radiative recombination, and cause the quantum well energy band to be flattened, and the electron-hole wave function to overlap more. At the same time, the Ga polarity relative to the N polarity can effectively improve the crystal quality of the quantum well, reduce the incorporation of impurities, improve the clarity of the interface, reduce the risk of leakage, and improve the effective composite luminescence efficiency of the combination layer 4.
[0047] Further explanation: the polarization field of the N-face polar quantum well layer 421, the N-face polar quantum barrier layer 422 and the N-face polar Si-doped InAlGaN layer 424 is in the same direction as the external electric field. The polarization field and the external electric field jointly accelerate the injection of electrons and holes into the well layer, and the carrier injection efficiency is further improved, which increases the luminous efficiency of the multi-quantum well and reduces the loss of the working voltage. The Ga-face polar AlGaN layer 423 in the combined layer can increase the barrier in stages to block the overflow of electrons; at the same time, the N-face polar Si-doped InAlGaN layer 424 in the combined layer is polarization doped, which can continuously reduce the working voltage, reduce the lattice mismatch between layers, and reduce the generation of defects, thereby improving the effective radiation recombination efficiency, and then improving the luminous efficiency. The electron trap layer 41 of the present technical solution is an alternating structure of a Mg-doped ScGaN layer 411 and a BGaN layer 412. Before the growth of the combined layer, the BGaN layer continuously distorts the penetrating dislocations of the underlying layer to reduce the extension of the dislocations, thereby improving the crystal quality of the combined layer and reducing the generation of piezoelectric polarization. In the Mg-doped ScGaN layer 411, Mg doping continuously consumes excess electrons. The Mg-doped ScGaN layer 411 can increase the barrier height, slow down the electron migration speed, and thereby improve the antistatic ability of the chip, thereby improving the luminous efficiency.
[0048] Further explanation, the thickness of the N-face polar Si-doped InAlGaN layer 424 is 3 to 3.5 nm, exemplarily 3 nm, 3.1 nm, 3.2 nm, 3.3 nm, 3.4 nm, 3.5 nm, but not limited thereto;
[0049] The doping concentration of Si element in the N-face polar Si-doped InAlGaN layer 424 is 1×10 14 ~5×10 16 atoms / cm 3 .
[0050] More preferably, when the N-face polar Si-doped InAlGaN layer 424 is periodically grown, the doping concentration of the Si element is a periodically decreasing pattern in the epitaxial growth direction, and the growth atmosphere is N2 or NH3 growth, which can reduce the operating voltage and the lattice mismatch between layers, reduce the generation of defects, and thus improve the effective radiation recombination efficiency.
[0051] Specifically, the doping concentration of Si element in the N-face polar Si-doped InAlGaN layer 424 is 1×10 14 ~5×10 16 atoms / cm 3 , exemplarily 1×10 14 , 2×10 14 , 3×10 14 , 5×10 14 ,7×10 14, 1×10 15 , 3×10 15 , 5×10 15 , 8×10 15 , 1×10 16 , 3×10 16 , 5×10 16 atoms / cm 3 .
[0052] Further explanation, the proportion of Al component in the Ga-face polar AlGaN layer 423 is 0-0.3, and in the periodic growth, the Al component in the Ga-face polar AlGaN layer 423 presents a gradually increasing trend in each period;
[0053] The Ga-face polar AlGaN layer 423 has a thickness of 0-110 nm.
[0054] Preferably, in the periodically grown Ga-face polar AlGaN layer 423, the Al composition is grown in a gradient mode from 0 to 0.3, that is, the Al composition linearly changes from 0 to 0.3, which can gradually increase the potential barrier, block electron overflow, and further improve the luminescence efficiency of the nitride light-emitting diode epitaxial wafer.
[0055] Preferably, the thickness of the Ga-face polarity AlGaN layer 423 is in the range of 0 to 110 nm. During the periodic growth, the thickness of the Ga-face polarity AlGaN layer 423 gradually decreases with a thickness decrease range of 5 to 10 nm. The growth atmosphere is H2.
[0056] Further explanation, the N-face polar quantum well layer 421 is an InGaN layer with a thickness of 2 to 3.5 nm, exemplarily 2 nm, 2.2 nm, 2.5 nm, 2.8 nm, 3 nm, 3.3 nm, 3.5 nm, but not limited thereto; the growth atmosphere of the N-face polar quantum well layer 421 is N2, NH3 growth;
[0057] The N-face polar quantum barrier layer 422 is an HGaN layer, and H is a combination of any one or more of In, Al, B, Sc and Y; exemplarily, H is In, that is, the N-face polar quantum barrier layer 422 is an InGaN layer; H is Al, that is, the N-face polar quantum barrier layer 422 is an AlGaN layer; H is B, that is, the N-face polar quantum barrier layer 422 is a BGaN layer; H is Sc, that is, the N-face polar quantum barrier layer 422 is a ScGaN layer; H is Y, that is, the N-face polar quantum barrier layer 422 is a YGaN layer; H is a combination of In and Al, that is, the N-face polar quantum barrier layer 422 is an InAlGaN layer, but is not limited thereto.
[0058] The thickness of the N-side polar quantum barrier layer 422 is 9-16 nm, and exemplary thicknesses are 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, and 16 nm, but not limited thereto.
[0059] Further explanation: the thickness of the Mg-doped ScGaN layer 411 is 3-5 nm, and the doping concentration of the Mg element in the Mg-doped ScGaN layer 411 is 1×10 14 ~1×10 16 atoms / cm 3 .
[0060] Preferably, the doping concentration of the Mg element in the Mg-doped ScGaN layer 411 is in a periodic increasing pattern in the epitaxial growth direction, and the growth atmosphere is H2, N2, or NH3.
[0061] The thickness of the BGaN layer 412 is 3-5 nm, and exemplary thicknesses are 3 nm, 3.5 nm, 4 nm, 4.5 nm, and 5 nm, but not limited thereto.
[0062] Further explanation, the number of cycles of the alternating growth of the electron trap layer 41 is 3 to 6, exemplarily 3, 4, 5, 6, but not limited thereto;
[0063] The number of cycles of the alternating growth of the polarization layer 42 is 7 to 11, exemplarily 7, 8, 9, 10, and 11, but not limited thereto.
[0064] The growth temperature of the composite layer 4 is 780-1000°C, and the growth pressure is 100-500torr. The growth temperature of the composite layer 4 is exemplarily 780°C, 800°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, but not limited thereto; the growth pressure of the composite layer 4 is exemplarily 100torr, 120torr, 150torr, 180torr, 200torr, 220torr, 250torr, 280torr, 300torr, 320torr, 350torr, 380torr, 400torr, 420torr, 450torr, 480torr, 500torr, but not limited thereto.
[0065] A method for preparing a nitride light-emitting diode epitaxial wafer, used for preparing the above-mentioned nitride light-emitting diode epitaxial wafer, comprises the following steps:
[0066] (1) providing a substrate 1;
[0067] (2) depositing a buffer layer 2 on the substrate 1;
[0068] (3) depositing an N-type layer 3 on the buffer layer 2;
[0069] (4) depositing a combined layer 4 on the N-type layer 3;
[0070] (5) depositing an electron blocking layer 5 on the combined layer 4;
[0071] (6) A P-type layer 6 is deposited on the electron blocking layer 5 .
[0072] Specifically, the substrate 1 of the present technical solution can be selected from one of a sapphire substrate, a SiO2-sapphire composite substrate, a silicon substrate, a silicon carbide substrate, a gallium nitride substrate and a zinc oxide substrate.
[0073] Preferably, the substrate is a sapphire substrate, which is currently the most commonly used GaN-based LED substrate material. Sapphire substrates have the advantages of mature preparation technology, low price, easy cleaning and processing, and sapphire substrates have good stability at high temperatures.
[0074] Specifically, the buffer layer 2 of the present technical solution is an AlN buffer layer or a GaN buffer layer, and the thickness of the buffer layer 2 is 10 to 50 nm.
[0075] Preferably, an AlN buffer layer with a thickness of 15 nm is deposited in Applied Materials PVD. The AlN buffer layer provides nucleation centers with the same orientation as the substrate, releases the stress caused by the lattice mismatch between GaN and the substrate and the thermal stress caused by the mismatch in thermal expansion coefficients, provides a flat nucleation surface for further growth, reduces the contact angle of nucleation growth, and enables the island-like grown GaN grains to be connected into a surface within a smaller thickness, thereby transforming into two-dimensional epitaxial growth.
[0076] Further explanation, before depositing the N-type layer 3 on the buffer layer 2 in step (3), the step further includes a step of pre-treating the substrate 1 on which the buffer layer 2 has been deposited. The method of pre-treating is as follows:
[0077] The substrate 1 on which the buffer layer 2 has been plated is transferred into the MOCVD device and pretreated in H2 atmosphere for 1 to 10 minutes at a treatment temperature of 1000 to 1200°C; the substrate 1 is then nitrided by introducing NH3 at a temperature of 1000 to 1200°C for 1 to 10 minutes. This technical solution can improve the crystal quality of the buffer layer 2 by pretreating the substrate 1 on which the buffer layer 2 has been deposited, and can effectively improve the crystal quality of the subsequently deposited GaN epitaxial layer.
[0078] Further explanation, the N-type layer 3 includes a non-doped GaN layer (not shown in the figure) and a Si-doped n-type GaN layer (not shown in the figure), and step (3) of depositing the N-type layer 3 on the buffer layer 2 includes the following steps:
[0079] a. Depositing the non-doped GaN layer on the buffer layer 2; wherein the growth temperature of the non-doped GaN layer is 1050° C. to 1200° C., the growth pressure is 100 to 600 torr, and the thickness is 1 to 5 μm;
[0080] b. Depositing the Si-doped n-type GaN layer on the non-doped GaN layer; wherein the Si-doped n-type GaN layer has a growth temperature of 1050° C. to 1200° C., a growth pressure of 100 torr to 600 torr, a thickness of 2 to 3 μm, and a Si doping concentration of 1×10 19 ~5×10 19 atoms / cm 3 .
[0081] Preferably, the growth temperature of the non-doped GaN layer is 1100°C, the growth pressure is 150torr, and the growth thickness is 2-3μm. The growth temperature of the non-doped GaN layer is high, the pressure is low, and the prepared GaN crystal quality is better. At the same time, as the thickness of GaN increases, the compressive stress will be released through stacking faults, the line defects will be reduced, the crystal quality will be improved, and the reverse leakage will be reduced. However, increasing the thickness of the non-doped GaN layer consumes a lot of Ga source materials, which greatly increases the epitaxy cost of the LED. Therefore, preferably, the growth thickness of the non-doped GaN layer is 2-3μm, which not only saves production costs, but also the GaN material has a higher crystal quality.
[0082] Preferably, the growth temperature of the Si-doped n-type GaN layer is 1120°C, the growth pressure is 100 torr, the growth thickness is 2-3 μm, and the Si doping concentration is 2.5×10 19 atoms / cm 3 First, the Si-doped n-type GaN layer provides sufficient electrons for LED light emission. Secondly, the resistivity of the Si-doped n-type GaN layer is higher than that of the transparent electrode on the p-GaN. Therefore, sufficient Si doping can effectively reduce the resistivity of the Si-doped n-type GaN layer. Finally, sufficient thickness of Si-doped n-type GaN can effectively release stress, thereby improving the luminous efficiency of the light-emitting diode.
[0083] Further explanation, in step (5), the electron blocking layer 5 is an AlInGaN layer, the Al component in the electron blocking layer 5 accounts for 0.005-0.1, and the In component accounts for 0.01-0.2;
[0084] The thickness of the electron blocking layer 5 is 10-40 nm, the growth temperature is 900-1000° C., and the pressure is 100-300 torr.
[0085] Preferably, the electron blocking layer is AlInGaN with a thickness of 15 nm, wherein the Al component concentration gradually changes from 0.01 to 0.05 along the growth direction of the epitaxial layer, the In component concentration is 0.01, the growth temperature is 965°C, and the growth pressure is 200 torr, which can effectively limit electron overflow and reduce the blocking of holes, thereby improving the injection efficiency of holes into the quantum well, reducing carrier Auger recombination, and improving the luminous efficiency of the light-emitting diode.
[0086] To further illustrate, in step (6), the P-type layer 6 is a P-type GaN layer.
[0087] Specifically, the growth temperature of the P-type GaN layer is 900-1050°C, the thickness is 10-50 nm, the growth pressure is 100-600 torr, and the Mg doping concentration is 1×10 19 ~1×10 21 atoms / cm 3 .
[0088] Preferably, the growth temperature of the P-type GaN layer is 985°C, the thickness is 15 nm, the growth pressure is 200 torr, and the Mg doping concentration is 2×10 20 atoms / cm 3 Too high a Mg doping concentration will damage the crystal quality, while a low doping concentration will affect the hole concentration. At the same time, for LED structures containing V-shaped pits, the higher growth temperature of the P-type GaN layer is also conducive to merging the V-shaped pits and obtaining LED epitaxial wafers with smooth surfaces.
[0089] The technical scheme of the present invention is further described below through examples and comparative examples.
[0090] In the following embodiments and comparative examples, a SMIC A7 MOCVD (Metal-organic Chemical Vapor Deposition, MOCVD for short) device was used, high-purity H2 (hydrogen), high-purity N2 (nitrogen), or a mixed gas of high-purity H2 and high-purity N2 was used as a carrier gas, high-purity NH3 was used as an N source, trimethylgallium (TMGa) and triethylgallium (TEGa) were used as gallium sources, trimethylindium (TMIn) was used as an indium source, trimethylaluminum (TMAl) was used as an aluminum source, silane (SiH4) was used as an N-type dopant, the B source was derived from Bcl3, the Sc source was derived from CP3Sc, and bis(cyclopentadienyl)magnesium (CP2Mg) was used as a P-type dopant for epitaxial growth.
[0091] Example 1
[0092] The nitride light-emitting diode epitaxial wafer of this embodiment includes a substrate 1, and a buffer layer 2, an N-type layer 3, a combination layer 4, an electron blocking layer 5 and a P-type layer 6 sequentially stacked on the substrate 1;
[0093] The combined layer 4 includes an electron trap layer 41 and a polarization layer 42 which are stacked and grown sequentially from bottom to top;
[0094] The electron trap layer 41 includes a Mg-doped ScGaN layer 411 and a BGaN layer 412 that are periodically and alternately grown from bottom to top, with an alternating growth period of 5; the polarization layer 42 includes an N-face polarity quantum well layer 421, an N-face polarity quantum barrier layer 422, a Ga-face polarity AlGaN layer 423 and an N-face polarity Si-doped InAlGaN layer 424 that are periodically and alternately grown from bottom to top, with an alternating growth period of 10.
[0095] Wherein, the N-side polar quantum well layer 421 is an InGaN layer with a thickness of 3 nm;
[0096] The N-face polar quantum barrier layer 422 is an HGaN layer, where H is Sc, that is, the N-face polar quantum barrier layer 422 is an ScGaN layer; the thickness of the N-face polar quantum barrier layer 422 is 12 nm;
[0097] The proportion of Al component in the Ga-face polar AlGaN layer 423 is 0-0.3, and the Al component in the periodic growth of the Ga-face polar AlGaN layer 423 grows in a gradient mode of 0 to 0.3, that is, the Al component linearly changes from 0 to 0.3; the thickness of the Ga-face polar AlGaN layer 423 is 10-100nm, and in the periodic growth, the thickness of the Ga-face polar AlGaN layer 423 gradually decreases, and the thickness decreases by 10nm, that is, the thickness of the Ga-face polar AlGaN layer 423 in each period is 100nm, 90nm, 80nm, 70nm, 60nm, 50nm, 40nm, 30nm, 20nm, and 10nm respectively;
[0098] The thickness of the N-face polar Si-doped InAlGaN layer 424 is 3 nm, and the doping concentration of Si element is 3×10 15 ~8×10 15 atoms / cm 3 ; and when the N-face polar Si-doped InAlGaN layer 424 is periodically grown, the doping concentration of the Si element increases from 8×10 15 atoms / cm 3 Periodically decreases to 3×10 15 atoms / cm 3 ;
[0099] The thickness of the Mg-doped ScGaN layer 411 is 4 nm, and the doping concentration of the Mg element is 8×10 14 ~5×10 15 atoms / cm 3In the periodically grown Mg-doped ScGaN layer 411, the doping concentration of the Mg element increases from 8×10 14 atoms / cm 3 Periodically increase to 5×10 15 atoms / cm 3 ;
[0100] The thickness of the BGaN layer 412 is 4 nm.
[0101] The method for preparing the nitride light-emitting diode epitaxial wafer of this embodiment comprises the following steps:
[0102] (1) providing a substrate 1, wherein the substrate is a sapphire substrate;
[0103] (2) depositing a buffer layer 2 (AlN buffer layer) on the substrate 1, wherein the thickness of the buffer layer 2 is 15 nm;
[0104] (3) comprising the following steps:
[0105] (3.1) Pre-treating the substrate 1 on which the buffer layer 2 has been deposited. The pre-treating method is as follows: transferring the substrate 1 on which the buffer layer 2 has been deposited into the MOCVD device, pre-treating it in a H2 atmosphere for 6 minutes at a treatment temperature of 1020°C, and then nitriding the substrate 1 by introducing NH3 at a temperature of 1100°C for 5 minutes;
[0106] (3.2) Depositing an N-type layer 3 on the buffer layer 2, wherein the N-type layer 3 includes an undoped GaN layer and a Si-doped n-type GaN layer. Depositing the N-type layer 3 on the buffer layer 2 includes the following steps:
[0107] a. Depositing a non-doped GaN layer on the buffer layer 2; wherein the growth temperature of the non-doped GaN layer is 1100° C., the growth pressure is 150 torr, and the thickness is 3 μm;
[0108] b. Deposit a Si-doped n-type GaN layer on the non-doped GaN layer; wherein the growth temperature of the Si-doped n-type GaN layer is 1120°C, the growth pressure is 100 torr, the thickness is 3 μm, and the Si doping concentration is 2.5×10 19 atoms / cm 3 .
[0109] (4) depositing a composite layer 4 on the N-type layer 3; wherein the growth temperature of the composite layer 4 is 980° C. and the growth pressure is 200 torr;
[0110] (5) depositing an electron blocking layer 5 on the combined layer 4; wherein the electron blocking layer 5 is an AlInGaN layer, the proportion of Al component in the electron blocking layer 5 is 0.01-0.05, and the concentration of Al component gradually changes from 0.01 to 0.05 along the growth direction of the epitaxial layer, and the proportion of In component is 0.01; the thickness of the electron blocking layer 5 is 15 nm, the growth temperature is 965° C., and the pressure is 200 torr;
[0111] (6) A P-type layer 6 is deposited on the electron blocking layer 5; wherein the P-type layer 6 is a P-type GaN layer, the growth temperature of the P-type GaN layer is 985° C., the thickness is 15 nm, the growth pressure is 200 torr, and the Mg doping concentration is 2×10 20 atoms / cm 3 .
[0112] Example 2
[0113] This embodiment provides a nitride light-emitting diode epitaxial wafer, the structure and preparation method of which are basically the same as those of Embodiment 1, except that:
[0114] The N-side polar quantum well layer 421 of this embodiment is an InGaN layer with a thickness of 2 nm;
[0115] The N-face polar quantum barrier layer 422 is a HGaN layer, where H is Al, that is, the N-face polar quantum barrier layer 422 is an AlGaN layer; the thickness of the N-face polar quantum barrier layer 422 is 9 nm;
[0116] The proportion of Al component in the Ga-face polar AlGaN layer 423 is 0-0.3, and the Al component in the periodic growth of the Ga-face polar AlGaN layer 423 grows in a gradient mode of 0 to 0.3, that is, the Al component linearly changes from 0 to 0.3; the thickness of the Ga-face polar AlGaN layer 423 is 35-80nm, and in the periodic growth, the thickness of the Ga-face polar AlGaN layer 423 gradually decreases, and the thickness decreases by 5nm, that is, the thickness of the Ga-face polar AlGaN layer 423 in each period is 80nm, 75nm, 70nm, 65nm, 60nm, 55nm, 50nm, 45nm, 40nm, and 35nm respectively;
[0117] The thickness of the N-face polar Si-doped InAlGaN layer 424 is 3.5 nm, and the doping concentration of Si element is 5×10 15 ~9.3×10 15 atoms / cm 3 ; and when the N-face polar Si-doped InAlGaN layer 424 is periodically grown, the doping concentration of the Si element increases from 9.3×10 15 atoms / cm 3 Periodically decreases to 5×1015 atoms / cm 3 ;
[0118] The thickness of the Mg-doped ScGaN layer 411 is 3 nm, and the doping concentration of the Mg element is 2×10 15 atoms / cm 3 ; The thickness of the BGaN layer 412 is 5 nm.
[0119] Example 3
[0120] This embodiment provides a nitride light-emitting diode epitaxial wafer, the structure and preparation method of which are basically the same as those of Embodiment 1, except that:
[0121] In step a, the growth temperature of the non-doped GaN layer is 1050° C., the growth pressure is 100 torr, and the thickness is 2 μm;
[0122] In step b, the growth temperature of the Si-doped n-type GaN layer is 1180°C, the growth pressure is 200 torr, the thickness is 2 μm, and the Si doping concentration is 1.5×10 19 atoms / cm 3 .
[0123] Comparative Example 1
[0124] This comparative example is a commercially available nitride light-emitting diode epitaxial wafer, which includes a substrate, a buffer layer, an N-type layer, a multi-quantum well layer, an electron blocking layer and a P-type layer from bottom to top.
[0125] Comparative Example 2
[0126] This comparative example provides a nitride light-emitting diode epitaxial wafer, the structure and preparation method of which are basically the same as those of Example 1, except that:
[0127] In this comparative example, the proportion of Al component in the Ga-face polar AlGaN layer 423 in each period is 0.1, and the thickness is 30 nm.
[0128] Performance Test:
[0129] The nitride light-emitting diode epitaxial wafers obtained in Examples 1-3 and Comparative Examples 1-2 were prepared into 10mil*24mil LED chips using the same chip process conditions. 300 LED chips were extracted from each sample, and their luminous efficiency was tested at a working current of 120mA. Based on Comparative Example 1, the luminous efficiency improvement rate in each Example and Comparative Example was calculated:
[0130] Light efficiency improvement rate = (improved light efficiency - original light efficiency) / original light efficiency × 100%;
[0131] In the above calculation formula: the original light effect is the light effect of comparative example 1.
[0132] Specifically, the test results are shown in Table 1 below:
[0133] Table 1 Performance test results of Examples 1-4 and Comparative Examples 1-5
[0134] Light efficiency improvement rate Example 1 1.85% Example 2 1.59% Example 3 1.63% Comparative Example 1 —— Comparative Example 2 1.42%
[0135] It can be seen from the above experimental data that, compared with the conventional LED epitaxial structure of comparative example 1, which uses a multi-quantum well layer between the N-type layer and the electron blocking layer, the nitride light-emitting diode epitaxial wafer of the present technical solution improves and optimizes the overall structure, and sets a combination layer 4 between the N-type layer 3 and the electron blocking layer 5. Among them, the combination layer 4 includes an electron trap layer 41 and a polarization layer 42 that are stacked and grown sequentially from bottom to top; the electron trap layer 41 is an alternating structure of a Mg-doped ScGaN layer 411 and a BGaN layer 412; the polarization layer 42 includes an N-face polarity quantum well layer 421, an N-face polarity quantum barrier layer 422, a Ga-face polarity AlGaN layer 423, and an N-face polarity Si-doped InAlGaN layer 424 that are periodically and alternately grown sequentially from bottom to top. This technical solution can increase the effective recombination efficiency of holes and electrons, reduce electron overflow and reduce the Stark efficiency of multiple quantum wells by improving and optimizing the structure of the epitaxial wafer, thereby improving the luminous efficiency. Compared with the LED chip prepared in comparative example 1, the photoelectric efficiency of the LED chips prepared in examples 1-3 is improved by 1.59% to 1.85%. In addition, other electrical properties are good.
[0136] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A nitride light-emitting diode epitaxial wafer, comprising a substrate, characterized in that: It also includes a buffer layer, an N-type layer, a combination layer, an electron blocking layer and a P-type layer stacked in sequence on the substrate; The combined layer includes an electron trap layer and a polarization layer which are stacked and grown sequentially from bottom to top; The electron trap layer includes a Mg-doped ScGaN layer and a BGaN layer that are periodically and alternately grown from bottom to top; The polarization layer comprises an N-face polarity quantum well layer, an N-face polarity quantum barrier layer, a Ga-face polarity AlGaN layer and an N-face polarity Si-doped InAlGaN layer which are grown periodically and alternately from bottom to top.
2. The nitride light emitting diode epitaxial wafer according to claim 1, characterized in that: The thickness of the N-face polar Si-doped InAlGaN layer is 3 to 3.5 nm; The doping concentration of Si element in the N-face polar Si-doped InAlGaN layer 424 is 1×10 14 ~5×10 16 atoms / cm 3 .
3. The nitride light emitting diode epitaxial wafer according to claim 1, characterized in that: The proportion of Al component in the Ga-face polar AlGaN layer is 0-0.3, and in the periodic growth, the Al component in the Ga-face polar AlGaN layer presents an increasing trend in each period; The thickness of the Ga-face polar AlGaN layer is 0-110 nm.
4. The nitride light emitting diode epitaxial wafer according to claim 1, characterized in that: The N-side polar quantum well layer is an InGaN layer with a thickness of 2 to 3.5 nm; The N-side polar quantum barrier layer is a HGaN layer, and H is any one or more combinations of In, Al, B, Sc and Y; the thickness of the N-side polar quantum barrier layer is 9-16 nm.
5. The nitride light emitting diode epitaxial wafer according to claim 1, characterized in that: The thickness of the Mg-doped ScGaN layer is 3-5 nm, and the doping concentration of the Mg element in the Mg-doped ScGaN layer is 1×10 14 ~1×10 16 atoms / cm 3 ; The thickness of the BGaN layer is 3-5 nm.
6. The nitride light emitting diode epitaxial wafer according to claim 1, characterized in that: The number of cycles of the alternating growth of the electron trap layers is 3 to 6; The number of cycles of the alternating growth of the polarization layers is 7 to 11; The growth temperature of the combined layer is 780-1000° C., and the growth pressure is 100-500 torr.
7. The nitride light emitting diode epitaxial wafer according to claim 1, characterized in that: The electron blocking layer is an AlInGaN layer, in which the Al component accounts for 0.005-0.1, and the In component accounts for 0.01-0.2; The thickness of the electron blocking layer 5 is 10-40 nm, the growth temperature is 900-1000° C., and the pressure is 100-300 torr.
8. A method for preparing a nitride light-emitting diode epitaxial wafer, characterized in that: The method for preparing the nitride light-emitting diode epitaxial wafer according to any one of claims 1 to 7 comprises the following steps: (1) providing a substrate; (2) depositing a buffer layer on the substrate; (3) depositing an N-type layer on the buffer layer; (4) depositing a combined layer on the N-type layer; (5) depositing an electron blocking layer on the combined layer; (6) Depositing a P-type layer on the electron blocking layer.
9. The method for preparing a nitride light emitting diode epitaxial wafer according to claim 8, characterized in that: Step (3) before depositing the N-type layer on the buffer layer, further includes the step of pre-treating the substrate on which the buffer layer has been deposited, wherein the pre-treating method is as follows: The substrate coated with the buffer layer is transferred into the MOCVD device, pretreated for 1 to 10 minutes in a H2 atmosphere at a treatment temperature of 1000 to 1200°C, and then the substrate is nitrided.
10. The method for preparing a nitride light emitting diode epitaxial wafer according to claim 8, characterized in that: The N-type layer includes an undoped GaN layer and a Si-doped n-type GaN layer. Step (3) of depositing the N-type layer on the buffer layer includes the following steps: a. Depositing the non-doped GaN layer on the buffer layer; wherein the growth temperature of the non-doped GaN layer is 1050° C. to 1200° C., the growth pressure is 100 to 600 torr, and the thickness is 1 to 5 μm; b. Depositing the Si-doped n-type GaN layer on the non-doped GaN layer; wherein the Si-doped n-type GaN layer has a growth temperature of 1050° C. to 1200° C., a growth pressure of 100 torr to 600 torr, a thickness of 2 to 3 μm, and a Si doping concentration of 1×10 19 ~5×10 19 atoms / cm 3 .
Citation Information
Patent Citations
GaN green light emitting diode based on ScAlGaN ultra-strong polarization n-type layer and preparation method thereof
CN113471343A
Light emitting diode epitaxial wafer and preparation method thereof
CN114420807A
Light emitting diode epitaxial wafer and preparation method thereof
CN115863501A
Light emitting diode and preparation method thereof
CN116544327A
Epitaxial structure of high electron mobility transistor and preparation method thereof
CN117727782A
Cited By
Green Micro-LED epitaxial wafer, preparation method thereof and Micro-LED
CN121548148A